Study of inter-relationship of depression, seizure frequency and quality of life of people with epilepsy in India - Shubham Mehta; Alok Tyagi; Richa Tripathi; Mahesh Kumar (Mental Illness)
Epilepsy is a chronic neurological disorder that can have profound physical, social and psychological consequences. We aimed to assess the clinical predictors of quality of life of people with epilepsy. We recruited 31 patients suffering from epilepsy in this cross-sectional study. Their clinical profile was recorded. Quality Of Life in Epilepsy (QOLIE-31) was used to assess quality of life of our patients. Depression was screened by Neurological Disorders Depression Inventory in Epilepsy (NDDI-E). Among all the clinical variables, only seizure frequency significantly correlated with seizure worry (P=0.002), emotional well-being (P=0.026) and social functions (P=0.013) subscales of QOLIE-31. NDDI-E score showed a significant negative correlation with all the subscales of QOLIE-31 except medication effects (P=0.993). A significant positive correlation was also noted between seizure frequency and NDDI-E score (r=0.417, P=0.020). Seizure frequency and depression are the most important predictors of quality of life in epilepsy patients. The management of patients with epilepsy should not only be aimed at just preventing seizures but the treating clinicians should also be cognizant about depression which itself can significantly affect the quality of life of patients.